2013
DOI: 10.3748/wjg.v19.i48.9156
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic considerations for optimizing tacrolimus dosing in liver and kidney transplant patients

Abstract: The introduction of tacrolimus in clinical practice has improved patient survival after organ transplant. However, despite the long use of tacrolimus in clinical practice, the best way to use this agent is still a matter of intense debate. The start of the genomic era has generated new research areas, such as pharmacogenetics, which studies the variability of drug response in relation to the genetic factors involved in the processes responsible for the pharmacokinetics and/or the action mechanism of a drug in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 115 publications
0
87
0
3
Order By: Relevance
“…Although rapidly absorbed in the GI tract, the bioavailability of tacrolimus from the traditional twice-daily capsule formulation is low and variable, ranging from 17 to 23% [7]. The relatively low bioavailability of tacrolimus is believed to be due to a number of factors including poor water solubility, extensive first pass metabolism, p-glycoprotein-mediated efflux and the ingestion of food [15]. Tacrolimus twice-daily capsules are associated with a characteristic high peak (C max ) following dosing, which may be associated with increased toxicity [16][17][18].…”
mentioning
confidence: 99%
“…Although rapidly absorbed in the GI tract, the bioavailability of tacrolimus from the traditional twice-daily capsule formulation is low and variable, ranging from 17 to 23% [7]. The relatively low bioavailability of tacrolimus is believed to be due to a number of factors including poor water solubility, extensive first pass metabolism, p-glycoprotein-mediated efflux and the ingestion of food [15]. Tacrolimus twice-daily capsules are associated with a characteristic high peak (C max ) following dosing, which may be associated with increased toxicity [16][17][18].…”
mentioning
confidence: 99%
“…Nevertheless, transplant recipient pharmacogenomics could account in part for the high alphatorquevirus levels observed at the 2‐week time point among non‐white respondents in the current study: Genetic polymorphisms (eg, CYP3A4) that have a characteristic race‐specific distribution and which may impact tacrolimus metabolism were previously described . Moreover, in a study of the Cylex Immune Cell Function assay (a functional test of immune status occasionally used in lung transplant recipients), African Americans had lower immune function measures at all post‐transplant time points as compared to non‐African Americans .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, genome-wide association studies revealed different genetic susceptibility loci for SLE between ethnicity groups 45. Also, the CYP3A5 polymorphism determines the metabolism of TAC, and a lower bioavailability of TAC in African-American kidney transplant recipients46 47 is well described. Altogether emphasising that the extrapolation of these data to other ethnic groups is not self-evident.…”
Section: Discussionmentioning
confidence: 99%